1995
DOI: 10.1056/nejm199510053331404
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Tuberculosis in Patients without HIV Infection

Abstract: In this report from New York City, HIV-negative patients with multidrug-resistant tuberculosis, contrary to previous reports, responded well to appropriate chemotherapy, both clinically and microbiologically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
59
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(67 citation statements)
references
References 14 publications
7
59
1
Order By: Relevance
“…A subsequent study by Goble et al 20 indicated a 44% treatment failure rate among 134 evaluable patients. These results were contradicted in a study by Telzak et al 19 in which 24 of 25 MDRTB patients showed a clinical response to treatment. The difference between Telzak and colleagues' study and the previous experiments was that the subjects in Telzak and colleagues' study were earlier in the progression of TB.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…A subsequent study by Goble et al 20 indicated a 44% treatment failure rate among 134 evaluable patients. These results were contradicted in a study by Telzak et al 19 in which 24 of 25 MDRTB patients showed a clinical response to treatment. The difference between Telzak and colleagues' study and the previous experiments was that the subjects in Telzak and colleagues' study were earlier in the progression of TB.…”
mentioning
confidence: 76%
“…Most patients treated with 4-drug regimens test negative within 3 months of treatment initiation. 19 Patients who have developed MDRTB have a less favorable prognosis. In trials conducted by the British Medical Research Council, of 8 patients who had MDRTB, 5 failed treatment and 2 relapsed.…”
mentioning
confidence: 99%
“…A national molecular service for the identification of M. tuberculosis and the detection of rifampicin resistance in smear-positive sputum was instituted after Four studies in the USA [3,4,[25][26][27] had indicated a reduced mortality (even among HIV-positive individuals) as a result of early MDRTB detection and the institution of therapy based on in-vitro drug susceptibility testing. For example, in a study of 38 mainly HIV-positive MDRTB patients, an overall response rate of 50% was seen with a median survival of 315 days [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, a careful review of the three articles shows that there was no comparison, nor demonstration of better outcomes attributable to a higher number of administered drugs [24]. The only reasonable conclusion from these articles [21][22][23], as from a number of others [43][44][45][46][47][48][49], is that acceptable results are obtained prescribing more than four drugs. Nevertheless, it does not demonstrate that the use of fewer drugs would entail inferior results.…”
Section: Basis Of Tb Retreatment Regimen Developmentmentioning
confidence: 99%